Cream skimming by health care providers and inequality in health care access: Evidence from a randomized field experiment - Anna Werbeck; Ansgar Wübker; Nicolas R. Ziebarth (RWI - Leibniz-Institut für Wirtschaftsforschung, 2020)
Using a randomized field experiment, we show that health care specialists cream-skim patients by their expected profitability. In the German two-tier system, outpatient reimbursement rates for both public and private insurance are centrally determined but are more than twice as high for the privately insured. In our field experiment, following a standardized protocol, the same hypothetical patient called 991 private practices in 36 German counties to schedule appointments for allergy tests, hearing tests and gastroscopies. Practices were 7% more likely to offer an appointment to the privately insured. Conditional on being offered an appointment, wait times for the publicly insured were twice as long than for the privately insured. Our findings show that structural differences in reimbursement rates lead to structural differences in health care access. – – Basierend auf einem randomisierten Feldexperiment zeigt diese Studie, dass Fachärzte Patienten mit einer höheren erwarteten Profitabilität bevorzugen. Im deutschen Gesundheitssystem werden Erstattungssätze für ambulante Leistungen sowohl für gesetzlich als auch für privat Versicherte zentral festgelegt; für privat Versicherte sind diese allerdings oft mehr als doppelt so hoch wie für gesetzlich Versicherte. Im Rahmen des Feldexperiments fragte ein hypothetischer Patient, einem standardisierten Protokoll folgend, telefonisch Termine für Allergietests, Hörtests und Magenspiegelungen bei 991 Facharztpraxen in 36 deutschen Landkreisen an. Die Praxen boten den Privatversicherten mit 7% höherer Wahrscheinlichkeit einen Termin an. Gegeben, dass ein Termin angeboten wurde, waren die Wartezeiten für die gesetzlich Versicherten doppelt so lang wie für die privat Versicherten. Die Ergebnisse zeigen, dass strukturelle Unterschiede in den Erstattungssätzen zu strukturellen Unterschieden beim Zugang zur Gesundheitsversorgung führen.
Keywords: I14; I11; I18; 330; health care inequality; reimbursement rates; health care access; discrimination; cherry picking; gastroscopy; audiometry; allergy test; allergists; otorhinolaryngologist; gastroenterologist